The determination of finger-flexor critical force in rock climbers - Giles, D.; Chidley, J. B.; Taylor, N.; Torr, O.; Hadley, J.; Randall, T.; Fryer, S. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine if the mathematical model used for the estimation of critical force (CF) and the energy store component W' are applicable to intermittent isometric muscle actions of the finger flexors of rock climbers, using a multisession test. As a secondary aim, the agreement of estimates of CF and W' from a single-session test was also determined. The CF was defined as the slope coefficient, and W' was the intercept of the linear relationship between total "isometric work" (Wlim) and time to exhaustion (Tlim). Methods: Subjects performed 3 (separated by either 20 min or >24 h) tests to failure using intermittent isometric finger-flexor contractions at 45%, 60%, and 80% of their maximum voluntary contraction. Results: Force plotted against Tlim displayed a hyperbolic relationship; correlation coefficients of the parameter estimates from the work-time CF model were consistently very high (R2 > .94). Climbers' mean CF was 425.7 (82.8) N (41.0% [6.2%] maximum voluntary contraction) and W' was 30,882 (11,820) N·s. Good agreement was found between the single-session and multisession protocol for CF (intraclass correlation coefficient [ICC3,1] = .900; 95% confidence interval, .616-.979), but not for W' (ICC3,1 = .768; 95% confidence interval, .190-.949). Conclusions: The results demonstrated the sensitivity of a simple test for the determination of CF and W', using equipment readily available in most climbing gyms. Although further work is still necessary, the test of CF described is of value for understanding exercise tolerance and to determine optimal training prescription to monitor improvements in the performance of the finger flexors.